An Empirical Assessment of the Monetary Policy Credibility and Economic Growth Relationship: A GMM Approach on COMESA and ECOWAS Regions - Aboyitungiye Jean Baptiste; Moses Mathu (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2023)
The study aims to highlight the effect of the credibility of monetary policy on economic growth concerning the COMESA compared with the ECOWAS economies. Those groups of countries are reached throughout the monetary policy credibility measurement to get an insight into whether the monetary policy is at the origin of the economic growth level of the country. The dynamic panel data consists of 5 years, from 2015 to 2020, for 11 countries of COMESA and ECOWAS. The findings from the two-system-GMM approach show a significant positive effect of the monetary policy credibility on economic growth in the COMESA region. On the other hand, the monetary policy credibility has an insignificant impact on the economic growth in the ECOWAS region. The findings lead us to recommend to the policymakers of central banks to ensure that they choose the appropriate monetary policy to return to growth, full employment and price stability.